2008
DOI: 10.1021/es7026949
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Effects of Catalytic Diesel Particulate Filters: Conversion of PAHs versus Formation of Nitro-PAHs

Abstract: Diesel particulate filters (DPFs) are a promising technology to detoxify diesel exhaust. However, the secondary combustion of diesel soot and associated compounds may also induce the formation of new pollutants. Diesel soot is rated as carcinogenic to humans and also acts as a carrier for a variety of genotoxic compounds such as certain polycyclic aromatic hydrocarbons (PAHs) or nitrated PAHs (nitro-PAHs). Furthermore, diesel exhaust contains considerable amounts of nitric oxide (NO), which can be converted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 31 publications
(75 reference statements)
4
98
0
2
Order By: Relevance
“…Many automobile companies either in Japan or European countries are competitively developing modern Diesel cars equipped with different types of exhaust treatment such as a particulate trap/filter to detoxify diesel exhaust. Swiss researchers very recently investigated the secondary effects of catalytic diesel particulate filters on the coversion of polyaromatic hydrocarbons (PAHs) versus formation of nitro-polyaromatic hydrocarbons (nito-PAHs), whereby PAHs were reduced by using filters, while they noticed the formation of selected nitro-PAHs (Norbert V. Heeb et al 2008). Although our present investigation was performed on the DEP collected from an engine without using a filter, we have demonstrated significant amounts of vasodilative nitro compounds are consisted in DEP, and their hazardous effects on human health cannot be ignored because of the vast amount of DEP emitted into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Many automobile companies either in Japan or European countries are competitively developing modern Diesel cars equipped with different types of exhaust treatment such as a particulate trap/filter to detoxify diesel exhaust. Swiss researchers very recently investigated the secondary effects of catalytic diesel particulate filters on the coversion of polyaromatic hydrocarbons (PAHs) versus formation of nitro-polyaromatic hydrocarbons (nito-PAHs), whereby PAHs were reduced by using filters, while they noticed the formation of selected nitro-PAHs (Norbert V. Heeb et al 2008). Although our present investigation was performed on the DEP collected from an engine without using a filter, we have demonstrated significant amounts of vasodilative nitro compounds are consisted in DEP, and their hazardous effects on human health cannot be ignored because of the vast amount of DEP emitted into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The carbonyl functionalisation rate is twice lower, ranging from 0.3 to 0.5% (Table 2). Compared to the other samples, the large nitro content may be linked to the high temperatures of the combustion processes occuring in the vehicle engines (Matthews, 1980;Eberhardt et al, 2003) and can be partially attributed to nitro-PAHs, previously identified in diesel exhaust OA (Heeb et al, 2008). The low content in functional groups containing oxygen atoms (carbonyl and carboxylic acid) is also consistent with the moderate water soluble organic carbon (WSOC) fraction measured, which accounts for 20% of the OC measured inside the tunnel (El Haddad et al, 2009) and with the hydrophobic propreties of fresh vehicular exhaust soot particles previously described in the literature (Weingartner et al, 1997).…”
Section: Functional Groups Fingerprints Of Aerosol Sourcesmentioning
confidence: 99%
“…The majority of experiments are performed on chassis dynamometers under predetermined engine load; a heated hose transfers the exhaust from the tailpipe to full flow exhaust dilution tunnels, and therefore, the exhaust gases are collected at low temperature after being mixed and homogenised with the ambient air (with moderate dilution ratios ranging from 6 to 14) in the dilution tunnel, which is connected to a constant volume sampling system (CVS technique) [45,46]. Chassis dynamometers can also be equipped with dilution systems such as critical-flow Venturi dilution tunnels [47], ejection dilutors [48], or rotating disk diluters [49], but undiluted exhaust can also be directly collected through a sampling probe inserted inside the tailpipe, which is a less conventional method [50].…”
Section: Exhaust Sampling and Collection For Pahs Analysismentioning
confidence: 99%